Representation of Sacracy and Monumentality in the Architectural Transformation of Mandara Giri Agung Semeru Temple through Brick Tectonics (Case Study: Lumajang Hotel) - Anindya, Nabila; Mohammad, Sholahudin (Arty: Jurnal Seni Rupa, 2025)
With an emphasis on the integration of local cultural elements into contemporary spatial composition, this study explores the transformation of vertical forms and rhythmic patterns from the architecture of Pura Mandara Giri Semeru Agung into the interior design of Hotel Lumajang through brick tectonics. The design was focused on two primary areas: the lobby and the suite unit. A practice-based design research method was employed to develop a design prototype representing sacred, monumental, and aesthetic impressions. User perception was evaluated using a 5-point Likert scale questionnaire administered to 50 respondents, covering three main dimensions. The results indicated that the Sacrality dimension achieved an average score of 3.68; Monumentality & Cultural Values scored 4.02; and Visual Aesthetics scored 4.15. These findings suggest that the brick tectonic elements effectively conveyed a strong and positive spatial impression, particularly in terms of monumentality and visual aesthetics. This study affirms the potential of brick tectonics as a medium for cultural representation in interior decorative elements, enriching meaningful spatial experiences in contemporary public space.